Anencephaly and Severe Myelodysplasia in a Stillborn Brown Bear (Ursus arctos arctos) - Ana Balseiro; Laura Polledo; José Tuñón; Juan Francisco García Marín (Animals, 2022)
Malformations in the development of the neural tube have been described to be associated with different aetiologies, such as genetic factors, toxic plants, chemical products, viral agents, or hyperthermia. A twenty-four-year-old female Eurasian brown bear (Ursus arctos arctos), permanently in captivity and kept under food and management control, gave birth to a stillborn cub at the end of gestation. Several malformations resulting from the anomalous development of the neural tube, not previously reported in bears, were observed, such as anencephaly, hypoplasia, micromyelia, severe myelodysplasia, syringomyelia, and spina bifida. Multiple canal defects (e.g., absence) were also observed in the spinal cord. In some regions, the intradural nerve roots surrounded the spinal cord in a diffuse and continuous way. The aetiology remains unidentified, although the advanced age of the mother and/or folic acid deficit might have been the possible causes of this disorder. Supplements of folate given to the mother before and during early pregnancy may have reduced the incidence of neural tube defects. That supplementation should be considered when the reproduction of bears is to occur in captivity, in order to prevent the loss of future generations of this endangered species.